2010
DOI: 10.4037/ajcc2010204
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Intrabladder Pressure Measurement in Intensive Care

Abstract: BackgroundThe reliability of intrabladder pressure measurements obtained in nonsupine patients is unknown. Objectives To investigate the reliability of measurements of intrabladder pressure obtained with 30° head-of-bed elevation. Methods With patients supine, 30° head-of-bed elevation, and instillation of 0 and 25 mL physiological saline, intrabladder pressure was measured in 10 patients: twice by one nurse to assess intraobserver reliability and once by a different nurse to assess interobserver reliability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Put another way, differences greater than this amount should suggest true changes in (patho‐) physiology. Furthermore, esophageal manometry seems as robust as other commonly used intensive care unit (ICU) parameters, such as pulmonary artery catheter and bladder measurements of intra‐abdominal pressure (26). In terms of clinical use in the ICU, our data provide guidance for ICU practitioners as to a normal value of P Es in subjects with mild to moderate obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Put another way, differences greater than this amount should suggest true changes in (patho‐) physiology. Furthermore, esophageal manometry seems as robust as other commonly used intensive care unit (ICU) parameters, such as pulmonary artery catheter and bladder measurements of intra‐abdominal pressure (26). In terms of clinical use in the ICU, our data provide guidance for ICU practitioners as to a normal value of P Es in subjects with mild to moderate obesity.…”
Section: Discussionmentioning
confidence: 99%
“…This finding emphasizes the importance of establishing a trend rather then relying on a single measurement to make important management decisions. Studies have shown low inter‐ and intraobserver variability with use of the IVP method in people and critically ill dogs . In cats, no significant differences in measurements were obtained between the observers in a study of healthy cats using the IVP technique utilizing a water manometer …”
Section: Factors Affecting Iapmentioning
confidence: 97%
“…Vital to the understanding of IAH and ACS is the appreciation of the factors that may influence IAP readings, their reproducibility, and their dependability . In the past several years, as techniques for IAP measurement have evolved, multiple pitfalls have come to light and thus work has been done in the attempt to identify and eliminate many of these limitations . If a patient is incorrectly labeled as having IAH or ACS, interventions taken to reduce the pressure may subject the patient to increased morbidity, either from the intervention itself or from a delay in proper treatment for comorbid disease.…”
Section: Factors Affecting Iapmentioning
confidence: 99%
“…The end of the catheter was connected to clear, open-ended plastic tubing, and the level of the water column above the midaxillary line reflects IAP. [13] IAP is measured for the patients in various body positions; the supine (HOB-0, HOB-15, and HOB-30) followed by right lateral (HOB-0, HOB-15, and HOB-30), at least 4 hours apart over a 24-h period. Intra-abdominal hypertension is graded into four categories; Grade I: IAP 12-15 mmHg, Grade II: IAP 16-20 mmHg, Grade III: IAP 21-25 mmHg, and Grade IV: IAP > 25 mmHg.…”
Section: Interventionmentioning
confidence: 99%